LAND RESOURCES AND THEIR ROLE IN THE DEVELOPMENT OF RURAL AREAS (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article deals with the problems and gives the estimation of the tendencies of the modern stage ofdevelopment the agrarian sector of Ukraine’s economy. It is defined that action of new social-economic andgeopolitical factors caused the appearance the whole number of problems of branch development. Among them are thereduction of quantity of small farms and private peasant farms, inadequate development of countryside infrastructure,improving social welfare, increase revenues to community budgets.
Keywords: food security,arable lands, cattle –farming, agrarian reform, agricuture, farm